Flashcard Media and Early Childhood Letter Recognition Achievement: Media Kartu Flash dan Prestasi Pengenalan Huruf pada Anak Usia Dini - Hasbi Pical; Luluk Iffatur Rocmah (Academia Open, 2025)
General Background: Early childhood literacy development plays a fundamental role in preparing children for formal education, particularly in letter recognition as the foundation of reading skills. Specific Background: In many early childhood education settings, children still experience difficulties in identifying and differentiating alphabet letters due to limited use of engaging instructional media. Knowledge Gap: Although various learning media have been implemented in early childhood classrooms, limited classroom action research has systematically examined the use of flashcard media to address letter recognition difficulties in specific institutional contexts. Aims: This study aims to improve early childhood letter recognition skills through the implementation of flashcard media in classroom learning activities. Results: The findings indicate a consistent increase in children’s ability to recognize, mention, and differentiate alphabet letters across action cycles, demonstrating measurable progress from the initial condition to the final cycle. Novelty: The study provides contextual classroom action evidence on structured flashcard implementation within early childhood education settings. Implications: These results suggest that flashcard-based instructional strategies can serve as practical pedagogical alternatives for teachers to support foundational literacy development in early childhood classrooms. Keywords: Flashcard Media, Early Childhood Education, Letter Recognition, Classroom Action Research, Early Literacy Key Findings Highlights: Progressive improvement in alphabet identification across action cycles Increased student participation during structured card-based activities Measurable gains from baseline condition to final evaluation stage